HUBUNGAN KOMPONEN SISTEM PENGENDALIAN MANAJEMEN (QUALITY GOAL, QUALITY FEEDBACK, DAN QUALITY INCENTIVE) TERHADAP KINERJA KUALITAS DAN KONSEKUENSI TERHADAP KINERJA KEUANGAN1 - Jumaili, Salman; ., Gudono (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
This research aims to give empirical evidence about relationship management control system components with quality performance, and relationship quality performance with customer satisfaction and financial performance, and relationship customer satisfaction with financial performance. Data are collected via electronic mail survey from Indonesian manufacturings. Data analysis use by path analysis. The result indicates that the managers must consider quality goal, quality feedback, and quality incentive that positively increased quality performance of product, although relation for quality goal is not significant. Quality performance is positively associated with customer satisfaction. Furthemore, quality performance as non-financial measure is not significant positively associated with financial performance, and high rate of customer satisfaction is positively associated with financial performance.